The Impact of Collective Action on Economic Development: Empirical Evidence from Kerala, India - PATRICIA JUSTINO (World Development Vol. 34, No. 7, pp. 1254-1270, 2006, 2006)
Public participation is generally assumed to be a necessary if not fundamental condition for development. Most studies do not, however, question the kind and level of collective action that would be desirable. This paper provides a novel empirical analysis of the impact of collective action on economic development using data for South India. The paper models collective action as endogenous to economic development and distinguishes between its static and dynamic properties. The results show that while excessive activism may harm state income, collective action in the context of responsible bargaining systems may contribute toward increased economic development